A Thematic Literature Review on the Needs and Challenges of Convert Muslim Women Preachers in Malaysia - Kamal Azmi Abd Rahman; Nik Suhaida Nik Abdul Majid; Suhailiza Md. Hamdani; Mohd Faridh Hafez Mhd Omar; Marina Munira Abdul Mutalib; Roslizawati Mohd Ramly (Yayasan Dakwah Islamiah Malaysia, 2026)
Tier 4 (Non-Indexed Publication)